Sosialisasi Produk BSI Akad Murabahah Cicil Emas Bagi Masyarakat Desa Pagar Banyu, Kota Pagar Alam, Provinsi Sumatera Selatan - Aan Imarullah; Idwal B; Rahmat Putra Hasibuan (Jurnal Pengabdian Masyarakat, 2026)
Indonesia’s Islamic finance industry has grown rapidly over the past decade, yet disparities in financial literacy and inclusion between urban and rural populations remain evident. According to SNLIK OJK–BPS data, the financial literacy index in urban areas reaches 69.71%, while rural areas lag behind at 59.25%. Communities in rural regions and small towns, such as Pagar Banyu Village in Pagaralam, continue to face challenges in accessing and understanding Islamic financial products. These limitations are largely influenced by inadequate infrastructure, lower educational exposure, and limited access to reliable financial information. As a result, participation in Islamic banking despite its alignment with Islamic principles remains relatively low. Sustainable financial education and outreach programs are essential to address this gap. Initiatives supported by institutions such as OJK, Bank Indonesia (BI), and the Islamic Economic Society (MES) have shown measurable impact, contributing 21% to Islamic financial literacy and 33% to financial inclusion. One relevant product is BSI Cicil Emas, a murabahah-based gold installment financing scheme that offers transparent pricing, flexible terms, and sharia compliance. However, many community members still misunderstand the difference between profit margins in murabahah and interest in conventional loans, and some mistakenly perceive sharia installments as involving usury. This community service program aims to enhance public understanding of murabahah contracts, correct misconceptions about riba, and encourage the use of BSI Cicil Emas as a safe, transparent, and sharia-compliant investment option, while strengthening collaboration between Islamic financial institutions and the local community to support economic empowerment.